SUPPLY CHAIN MANAGEMENT IMPACT ON COMPANY’S FINANCIAL PERFORMANCE: EMPIRICAL EVIDENCE FROM INDONESIA - Nahar, Aida; Chariri, Anis; Jatmiko Wahyu Prabowo, Tri (International Journal of Supply Chain Management, 2020)
Abstract- The company's financial performance is a significant aspect which can be affected by supply chain management. By knowing the supply chain procedure and financial performance of a company, one will be able to know the financial condition, business development, and the cash flow embedded in the company as well as the profit and income from the results of the company's business. The company's financial performance is measured by the profitability ratio of Return on Assets. This study uses supply chain management that is consistently listed in the Jakarta Islamic Index (JII) for 2014-2018 periods and has complete data that can be processed and analyzed. The result of this study shows that Turn Over Inventory and Total Asset Turn Over have a positive and significant effect on Return on Assets, and Debt to Asset Ratio has a negative and significant effect on Return on Assets. But Current Ratio, Cash Turn Over, and Debt to Equity Ratio have no effect on Return on Assets.